Circulating Noncoding RNAs as Biomarkers of Cardiovascular Disease and Injury - Viereck, Janika; Thum, Thomas (Circulation research, 2017)
The discovery of thousands of noncoding RNAs (ncRNAs) has expanded our view on mammalian genomes and transcriptomes, as well as their organization and regulation. Accumulating evidence on aberrantly regulated ncRNAs, including short microRNAs, long ncRNAs and circular RNAs, across various heart diseases indicates that ncRNAs are critical contributors to cardiovascular pathophysiology. In addition, ncRNAs are released into the circulation where they are present in concentration levels that differ between healthy subjects and diseased patients. Although little is known about the origin and function of such circulating ncRNAs, these molecules are increasingly recognized as noninvasive and readily accessible biomarker for risk stratification, diagnosis and prognosis of cardiac injury, and multiple forms of cardiovascular disease. In this review, we summarize recent findings on biological characteristics of circulating ncRNAs and highlight their value as potential biomarker in selected pathologies of cardiovascular disease.